2009
DOI: 10.1177/1049732309350684
|View full text |Cite
|
Sign up to set email alerts
|

Practicing the Awareness of Embodiment in Qualitative Health Research: Methodological Reflections

Abstract: Although the importance of the researcher's embodiment has been noted in health and social sciences research, in many instances, more attention has been paid to the embodiment of the researched. Thus, more in-depth analysis of the embodied researcher can illuminate qualitative inquiry. The influence of the embodied researcher became visible in a recent critical ethnographic study examining the negotiation of religious, spiritual, and cultural plurality in health care. In this article, we do not present researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 28 publications
0
69
0
3
Order By: Relevance
“…In the last decade, attention to embodiment has received increased attention in philosophy (Campbell, Meynell, & Sherwin, 2009), science (Gallagher, 2005) and social science (Johnson, 1999). Research that focuses on embodiment has also garnered growing attention in qualitative research practice; indeed, some scholars have suggested the need to re-embody qualitative inquiry Sharma, Reimer-Kirkham, & Cochrane, 2009). …”
Section: Embodiment In Research Practicesmentioning
confidence: 99%
“…In the last decade, attention to embodiment has received increased attention in philosophy (Campbell, Meynell, & Sherwin, 2009), science (Gallagher, 2005) and social science (Johnson, 1999). Research that focuses on embodiment has also garnered growing attention in qualitative research practice; indeed, some scholars have suggested the need to re-embody qualitative inquiry Sharma, Reimer-Kirkham, & Cochrane, 2009). …”
Section: Embodiment In Research Practicesmentioning
confidence: 99%
“…For example, a remarkable transformation occurred biannually when a multipurpose room was refurbished to host a Sikh service for hospitalized patients. Characteristic of the tradition of a Gurudwara, the service was followed by a lunch that welcomed staff, family members and other visitors from the hospital (Sharma, Reimer‐Kirkham and Cochrane 2009).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This article extends knowledge about embodiment of a cane versus a walker for older homebound women. We recognized the dialectic spanning the observable “object body” (Sakalys, 2006, p. 17) of each woman who carried a cane and the “subject body …, the phenomenological body, the lived body” (Sakalys, 2006, p. 17) of each woman for whom the cane was a “third leg” or “part of me.” However, we did not consider potential influences of researcher embodiment on findings, such as the non-verbal communication of interviewers (Sharma, Reimer-Kirkham, & Cochrane, 2009) during dialogue with participants about “my cane” and “the walker.”…”
Section: Discussionmentioning
confidence: 99%